SEXUAL HARASSMENT OF WOMEN AT WORKPLACE: A SOCIETAL ISSUE IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
Sexual harassment refers to any unwanted, undesired, or uninvited sexual behaviour that is likely to offend, degrade, or intimidate. According to Articles 14, 15(1), and 16(2) of the Constitution, it is a fundamental right to be treated equally by men and women, and it is unlawful to violate this right. Certain fundamental and basic